Functional magnetic resonance imaging exploration of combined hand and speech movements in Parkinson's disease - Pinto, Serge; Mancini, Laura; Jahanshahi, Marjan; Thornton, John S.; Tripoliti, Elina; Yousry, Tarek A.; Limousin, Patricia (Movement disorders, 2011)
Among the repertoire of motor functions, although hand movement and speech production tasks have been investigated widely by functional neuroimaging, paradigms combining both movements have been studied less so. Such paradigms are of particular interest in Parkinson's disease, in which patients have specific difficulties performing two movements simultaneously. In 9 unmedicated patients with Parkinson's disease and 15 healthy control subjects, externally cued tasks (i.e., hand movement, speech production, and combined hand movement and speech production) were performed twice in a random order and functional magnetic resonance imaging detected cerebral activations, compared to the rest. F‐statistics tested within‐group (significant activations at P values < 0.05, familywise error corrected), between‐group, and between‐task comparisons (regional activations significant at P values < 0.001, uncorrected, with cluster size > 10 voxels). For control subjects, the combined task activations comprised the sum of those obtained during hand movement and speech production performed separately, reflecting the neural correlates of performing movements sharing similar programming modalities. In patients with Parkinson's disease, only activations underlying hand movement were observed during the combined task. We interpreted this phenomenon as patients' potential inability to recruit facilitatory activations while performing two movements simultaneously. This lost capacity could be related to a functional prioritization of one movement (i.e., hand movement), in comparison with the other (i.e., speech production). Our observation could also reflect the inability of patients with Parkinson's disease to intrinsically engage the motor coordination necessary to perform a combined task. © 2011 Movement Disorder Society